2003
DOI: 10.1046/j.1365-2125.2003.01793.x
|View full text |Cite
|
Sign up to set email alerts
|

A placebo‐controlled pharmacodynamic and pharmacokinetic interaction study between tamsulosin and acenocoumarol

Abstract: Aim To evaluate pharmacokinetic and pharmacodynamic interactions between tamsulosin and acenocoumarol. Methods Twelve healthy volunteers received tamsulosin 0.4 mg or placebo once daily for 9 days in a double-blind, cross-over study. On day 5 of each study period, a single 10-mg oral dose of racemic acenocoumarol was administered. Results The ratios (point estimates (90% confidence intervals)) of values in the presence and absence of tamsulosin were: AUC PT 1.01 (0.98, 1.03); maximum prothrombin time (Pt max )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Various studies have reported the AUC 0-48 and AUC 0-∞ values of acenocoumarol for 1, 4, 10 and 12 mg dose (Table 1(Tab. 1); References in Table 1: Huang et al, 2008[2]; Masche et al, 1999[3]; Popovic et al, 1994[4]; Rolan et al, 2003[6]; Sasso et al, 2012[8]; Sunkara et al, 2004[9]; Thijssen and Baars, 1983[10]; Thijssen and Hamulyàk, 1989[12]). No other information on AUC 0-48 and AUC 0-∞ were available with the 2, 8 and 16 mg dose.…”
Section: mentioning
confidence: 99%
“…Various studies have reported the AUC 0-48 and AUC 0-∞ values of acenocoumarol for 1, 4, 10 and 12 mg dose (Table 1(Tab. 1); References in Table 1: Huang et al, 2008[2]; Masche et al, 1999[3]; Popovic et al, 1994[4]; Rolan et al, 2003[6]; Sasso et al, 2012[8]; Sunkara et al, 2004[9]; Thijssen and Baars, 1983[10]; Thijssen and Hamulyàk, 1989[12]). No other information on AUC 0-48 and AUC 0-∞ were available with the 2, 8 and 16 mg dose.…”
Section: mentioning
confidence: 99%
“…Other limitation of this study could be the use of a single dose from 4 mg tablet of acenocoumarol, considering that AUC values of plasma concentrations versus time are proportional to the administered dose in a higher range [8-16mg]. Finally, similar to other oral anticoagulants, acenocoumarol exhibits a narrow therapeutic index [ 30 ] , therefore we recommend that any patient who switches between reference product and generic formulation should be carefully monitored according to the International Normalized Ratio (INR) [ 31 ] .…”
mentioning
confidence: 99%